The primary health care: true advocate of health - Soumya, Chippagiri (International Journal Of Community Medicine And Public Health, 2020)
The health care delivery system in India faces challenges due to disparity in geographical, cultural and economic aspects. Nonetheless, health is an issue which brings all humans under one umbrella. It is primary health care that lays the foundation on which health of the people are built and protected. Realizing the strengthens of the primary health care system is of utmost importance especially in the era of vaccinations and disease eliminations. This requires for the health system to move towards mass approach and heath protection concept sooner than later. And what better way than the primary health care system?